The Impact of Artificial Intelligence (AI) and Robotics on Higher Education - Syed Gulfraz Naqvi; Faisal Iqbal; Javaria Yousaf; Rimsha Tariq (Journal of Management Practices, Humanities and Social Sciences, 2023)
Long-term, Artificial Intelligence (AI) and robotics may have an outsized effect on universities. Understanding the full scope of this impact is complicated by the siloed nature of the relevant literature and the fluidity of key notions. This present study is intended to understand how and to AI can facilitate the higher education sector. Design fiction that vividly imagines scenarios of future use of artificial intelligence or robotics offers a way to explain and question the possibilities of technology. This paper details how we used a narrative literature review to create eight design fictions that illustrate the breadth of opportunities for AI and robots in education, administration, and investigation. They generate larger conversations by highlighting how they might teach higher-level skills, shift employee responsibilities, and address consequences for human agency and digitalization. The current study's findings outline the 8 fictions to outline the comprehensive understanding of the uses of IA in the academic sector of higher education. The narrative literature is reviewed extensively, emphasizing the social, ethical, pedagogical, and administrative concerns of automating via AI and robots in HE. Readers interested in challenging assumptions about the future are encouraged to go